Association between adiponectin single nucleotide polymorphisms and the risk of diabetic polyneuropathy - Noha M. Bakr; Noha A. Hashim; Nevin F. Ibrahim; Sara F. Saadawy (Scientific Reports)
Abstract Genetic factors play a significant role in the occurrence and clinical course of diabetic peripheral neuropathy (DPN). This research aimed to search the influence of adiponectin single nucleotide polymorphisms (SNPs) on the risk of developing and the severity of DPN in Egyptian patients. Adiponectin SNPs were genotype in 360 participants comprising diabetic sufferers with and without peripheral neuropathy and healthy volunteers via the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) approach. Regarding the + 45 T/G SNP, the TG/ and GG genotypes and the G allele were linked to an rised risk of DPN by comparing the DPN group with both the control and diabetic patients without peripheral neuropathy (DWPN) groups, and when comparing the DWPN group with the control group. Concerning + 276 G/T SNP, the GT genotype and T allele were linked to a declined risk of occuring DPN when comparing the DPN group with both other groups. Patients with DPN had greater frequencies of the GA genotype of the − 11,391 G/A SNP than individuals in the control group, while patients with DPN had greater frequencies of the AA genotype than patients in the DWPN group. Regarding clinic-pathological features, a meaningful rise in the mean values of fasting blood glucose (FBG), duration of the disease, and Toronto Clinical Neuropathy Severity Score (TCSS) were noted in the + 45 GG genotype and G allele carriers. Contrariwise, the + 276 TT genotype carriers had lower mean values for the same clinic-pathological features. For the T allele carriers, the same results were observed in case of duration of the disease and TCSS value. Our results concluded that adiponectin + 45 T/G SNP could be a risk factor considering DPN and the severity of the disease. The − 11391G/A SNP might be associated with DPN. In addition, + 276 G/T SNP could be a protective factor regarding DPN and the severity of the disease.